2017
DOI: 10.1016/j.jaci.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Are dust mite allergens more abundant and/or more stable than other Dermatophagoides pteronyssinus proteins?

Abstract: Capsule Summary RNA-seq and denaturation studies demonstrated that allergens are among the most highly expressed and stable proteins from Dermatophagoides pteronyssinus. The combination of high levels of transcription and stability for the major allergens Der p 1, Der p 2, and Der p 23 is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 17 publications
(9 reference statements)
1
39
0
Order By: Relevance
“…Perhaps the best‐known example is the house dust mite allergen, Der p 1, a proteolytic enzyme capable of cleaving CD23 (FcεRII, the low‐affinity IgE receptor) and CD25 (IL‐2 receptor α‐chain) expressed on the surface of some B cells, resulting in dysregulation of the immune response and induced production of IgE . The allergenicity of these proteins is not limited to their enzymatic activity, however, and both relative abundance and stability have been cited as of equal importance . Pyruvate kinases, enolases and aldolases have been shown to be abundant but heat‐labile proteins in fish and shrimp …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the best‐known example is the house dust mite allergen, Der p 1, a proteolytic enzyme capable of cleaving CD23 (FcεRII, the low‐affinity IgE receptor) and CD25 (IL‐2 receptor α‐chain) expressed on the surface of some B cells, resulting in dysregulation of the immune response and induced production of IgE . The allergenicity of these proteins is not limited to their enzymatic activity, however, and both relative abundance and stability have been cited as of equal importance . Pyruvate kinases, enolases and aldolases have been shown to be abundant but heat‐labile proteins in fish and shrimp …”
Section: Discussionmentioning
confidence: 99%
“…36 The allergenicity of these proteins is not limited to their enzymatic activity, however, and both relative abundance and stability have been cited as of equal importance. 37,38 Pyruvate kinases, enolases and aldolases have been shown to be abundant but heat-labile proteins in fish 22 and shrimp. 21 The objective of this work was to identify whether cross-reactive IgE-binding proteins were present in C and fish, which could explain the frequency of sensitizations to these foods.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between protein abundance and RNA-Seq data has been established, with some post-transcriptional cellular processes affecting this interpretation [63]. A study on European HDM allergen transcript levels using RNA-Seq data concluded that allergens have a higher level of abundance than nonallergens [64]; and their results were found to be to relatively similar to homologues identified in american HDM from a different study [65]. In particular, these dust mite allergen studies indicate that there is substantial correlation between RNA-Seq dependent abundance levels and a protein's allergen status.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence suggested that abundance and stability could be two such properties, but no rigorous statistical comparisons were available until a study of the dust mite Dermatophagoides pteronyssinus (Dp) combined transcriptomics with proteomics. 1 The Dp study measured transcription levels as a proxy for protein abundance and correlated the results with proteome-wide stability measurements using mass spectrometry. It was found that the mite allergens were as a population more stable and more highly expressed than Dp non-allergens.…”
mentioning
confidence: 99%